Overview Of The Implementation Of The Zoning System At The Port Of Ro-Ro Kuala Tungkal Jambi Province - Sri Kartini; Doharman Lumban Tungkup; Desti Yuvita Sari (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2023)
Zoning is the division or division of an area into several parts, according to the functions and management objectives.Therefore, it is necessary to implement a zoning system in accordance with applicable laws and regulations in order to carry out good transportation activities. But the fact is that the Kuala Tungkal port itself has not implemented a zoning system so that the division of the zone layout at the Ro-ro port is still not good.The method used to analyze the existing problems is the analysis of the zoning system according to the laws and regulations with existing conditions. Based on Ministerial Regulation Number 91 of 2021, a port that meets the standard consists of 5 zones. Zone A, Zone B, Zone C, Zone D and Zone E. However, currently Ro-ro Port only has 3 Zones and there are no weighbridges that are included in Zone B. Based on this analysis, it can be concluded that the Kuala Tungkal Ro-ro Port has not implemented a zoning system in accordance with statutory standards. Therefore, it is necessary to plan for additional zoning by utilizing the empty area around the port as a Development Plan Area for Zone B1 (weighbridge) Zone D and Zone E so that the Ro-ro Port becomes a more organized, orderly and orderly port in accordance with Ministerial Regulation No. 91 of 2021 concerning zoning in the port area used to serve transportation